Why students feel anxious in group work: an investigation into students’ perspectives on the sources of their anxious experiences in group work - Xethakis, Larry J.; Rupp, Michael; Plummer, Brendan R. B. (Frontiers in Education, 2024)
This large-scale, mixed-methods study aimed to uncover sources of learner anxiety when interacting in small groups in the language classroom. A secondary aim of the study was to examine relationships between these sources and learners' levels of small-group anxiety. Data was gathered from 1,344 learners enrolled in English classes at four universities in western Japan. Qualitative content analysis was employed to identify anxiety-inducing situations described in learner' responses, and categorize these situations based on the underlying source of anxiety. The analysis revealed two primary sources of small-group anxiety: interacting with other learners and L2 communication. The most prominent interaction-related situations were interacting with new people, expressing opinions, and uncomfortable silence, while those related to L2 communication were competence and proficiency, conveying meaning and understanding others. Levels of small-group anxiety were significantly related to the source of anxiety. Learners with a high level of anxiety were twice as likely to cite interaction as the source of their anxiety than learners with a low level of anxiety. The results suggest that interaction anxiety may be more salient than foreign language anxiety when language learners work in small groups, and that the impact of this form of social anxiety needs to be taken into consideration for learners to fully receive the benefits of group work.